Displacement, an Identity Crisis Metaphor: A Postcolonial Study of Kureishi's The Black Album - Rasool, Shamshad; Jamil, Amir; Iqbal, Tabassum (Pakistan Languages and Humanities Review, 2025)
This study aims to investigate how displacement functions as a metaphor for identity crisis, with a specific focus on identifying the relationship between geographical locations and identity formation. For this purpose, the study analyses Kureishi's The Black Album applying the theoretical framework of Bhabha, particularly his concept of "Third Space". It also investigates the factors responsible for identity crisis—liminality, hybridity, mimicry, interstices, fragmented self, and narcissism—which contribute to the construct or deconstruction of an individual's identity. The study employs Textual Analysis methodology, utilizing Latent Coding to discover the underlying meaning within the texts. The findings reveal that the characters voluntarily choose to displace themselves from their homelands to the host land in pursuit of their aspirations, dreams, and desires. They struggle to assimilate into the host culture by mimicking the lifestyles and norms of the foreign people. Their attempts to adopt foreign norms and lifestyles fail. They become hybrid individuals trapped in the vicious cycle of belongingness—caught between two worlds, belonging fully to neither. This in-between situation accentuates a profound identity crisis. The analysis also reveals that the characters face intense discrimination and marginalization in their journey of dislocation and attempted relocation.